Pengembangan Media Komik Digital Berbasis Aplikasi Canva pada Kelas III di Sekolah Dasar Negeri 064017 Medan Kecamatan Perjuangan - Riska Aulika; Apiek Gandamana; Ibrahim Gultom; Dody Feliks; Husna Tambunan (Lembaga Intelektual Muda (LIM) Maluku, 2023)
The purpose of this study is to develop digital comic media based on the Canva application, in terms of the feasibility and benefits of learning media in the research learning process used in this study is a type of research and development or Research and Development (R&D). The development of this media used procedures from ADDIE (Analysis, Design, Development, Implementation and Evaluation). The subjects in this study were 1 class teacher and 15 students who were directly involved in the teaching and learning process every day. As well as 1 material expert and 1 media expert. Data collection was carried out by means of: observation, questionnaires, interviews, and tests. The results showed that the Canva Application-Based Digital Comics media was